Power-referenced refractometer based on hybrid fiber grating - Dong, Xinyong (2014)
A power-referenced fiber refractometer based on a hybrid fiber grating formed by a tilted-fiber Bragg grating (TFBG) cascading by a chirped-fiber Bragg grating (CFBG) is proposed and experimentally demonstrated. The optical signal reflected by the CFBG passes twice through the TFBG that enhances sensitivity of the refractometer. In addition, the optical signal is propagating all the way in the fiber core so that the extra insertion loss is low. Refractive index measurement with sensitivity up to 597.2 μW/R.I.U. is achieved within the range from 1.333 to ~1.42. The maximum detectable refractive index is ~1.45.